An Immunohistochemical Study of the Insulin-, Glucagon-, Orexin A- and Ghrelin- Immunoreactive Cells in the Endocrine Pancreas of Guinea Pig - Yaman, Mine; Bayrakdar, Ali (Kafkas Univ, Veteriner Fakultesi Dergisi, 2013)
The present study was conducted to clarify the regional distribution and relative frequency of endocrine cells secreting insulin, glucagon, orexin A (OXA) and ghrelin in the pancreatic islets of guinea pig, by specific immunohistochemical methods. In the pancreatic islets, most of insulin-IR cells were detected in the central region, partially in mantle region. Glucagon-IR cells were located in the periphery of the pancreatic islets. In addition, they had lower frequency in the central region. OXA and ghrelin-IR cells were identifed in central and peripheral regions of the pancreatic islets. Clearly, OXA-IR cells exhibited a characteristic distribution pattern resemble to those for the glucagon-IR cells. However, ghrelin immunoreactivity exhibited a characteristic distribution pattern different from that of insulin-immunoreactive cells. In conclusion, some species-dependent unique distributions characteristics of endocrine cells in the pancreatic islets were observed in the guinea pig.
Kobay endokrin pankreasında insülin-, glukagon-, orexin A- ve ghrelin- immunoreaktif Hücrelerin immunohistokimyasal Çalışması
Keywords: Immunohistochemistry; Pancreas; Endocrine cell; Guinea pig